China and Africa : Expanding Economic Ties in an Evolving Global Context - Pigato, Miria (World Bank, Washington, DC, 2015)
Economic growth in Sub-Saharan Africa (SSA) has averaged roughly 5 percent per year over the past decade, improving living standards and bolstering human development indicators across the continent. Stronger public institutions, a supportive, private sector focused policy environment, responsible macroeconomic management, and a sustained commitment to structural reforms have greatly expanded opportunities for countries in SSA to participate in global markets. In recent years, many countries in the region have benefited from an increasingly favorable external environment, high commodity prices, and an especially strong demand for natural resources by emerging economies, particularly China. Over the longer term, leveraging Chinese investment to support broad-based growth will require policies designed to boost the competitiveness of sectors in which China s economic rebalancing may create a comparative advantage for SSA. To date, few African countries have been able to benefit from large-scale Chinese investment outside the resource sector. However, as China s growth slows and its economy shifts toward a more consumption-driven model, it is likely that global demand for resource imports will slow as well. Countries with the most heavily concentrated export mix, particularly in the mineral and oil sectors are the most vulnerable to China s economic rebalancing and should be ready to adopt measures to mitigate the impact of negative terms-of-trade shocks. By contrast, as wage rates in China continue to rise and firms refocus their attention on domestic demand, countries in SSA will be well positioned to exploit emerging opportunities for investment in export-oriented manufacturing. Ethiopia provides an instructive example, as its inexpensive yet relatively skilled labor force, coupled with the government s proactive efforts to court Chinese investors, have enabled Ethiopia to attract substantial investments in labor-intensive industries. Infrastructure enhancement, workforce development, and good-governance reforms offer a promising strategy for many countries in the region. Although the establishment of industrial zones has yielded mixed results, several salient success stories warrant careful attention. This report discusses how Africa could take advantage of the untapped opportunities offered by China s progressively intensifying investment and trade ties with SSA. It is hoped that this analysis will enrich the ongoing dialogue between policy makers, private firms, and civil society regarding China s increasingly important role in the growth and development of Sub-Saharan Africa.